Participants' perspective on a COVID-19 online vocal group stimulation for people with Parkinson's disease - Hallé, Marie-Christine; Delorme, Charline; Coulombe, Édith; Rekik, Ouswa; Verduyckt, Ingrid (Frontiers in Rehabilitation Sciences, 2022)
The COVID-19 related confinement and social distancing had negative consequences on the health of individuals living with Parkinson’s Disease (PD). In collaboration with a non-profit organization, we developed and implemented a daily online vocal stimulation group named “Musculation de la Voix” (MdlV) in April 2020. To better understand the potential of MdlV to diversify existing services available to people with PD experiencing vocal symptoms, this study aimed to explore participants’ experience and perception of MdlV in terms of participation, motivations, feelings, perceived changes, and appreciation. The 45 individuals who registered to the Summer 2020 Semester of MdlV were invited to complete an online ten-question survey. Responses to the four close-ended questions were analyzed using descriptive statistics while statements provided in response to the six open-ended questions were subjected to an inductive qualitative content analysis. 37 participants completed the survey. Results revealed that the sample of respondents was mostly constituted of individuals who were engaged in this activity since its very beginning (62,2%), participated daily (59,5%), intended to keep participating in the activity (97,3%), and had never received speech-language therapy (SLT) services before (72,97%). The qualitative analysis yielded one theme relating to prior services: “Previous SLT services are variable and perceived as beneficial but with limitations”, and three themes pertaining to MdlV: “Seeking improvement and support as initial motivations to engage in MdlV”, “Unanticipated benefits and desired gains catalyzing motivation to participate in MdlV”, and “Perceived limitations of MdlV and persisting needs”. Our study participants’ engagement and motivation towards MdlV as well as the benefits they perceived in relation to this activity suggest that an online vocal stimulation group may be a promising complement to currently limited SLT services. As limitations and persisting needs were also identified, future studies are required to elucidate what aspect of MdlV works, for whom and how.